Determining the Innovativeness of Nurses Who Engage in Activities That Encourage Innovative Behaviors - Marion Leary; George Demiris; J. Margo Brooks Carthon; Pamela Z. Cacchione; Subhash Aryal; Jose A. Bauermeister (MDPI AG, 2024)
Background: We sought to understand the innovativeness of nurses engaging in innovative behaviors and quantify the associated characteristics that make nurses more able to innovate in practice. We first compared the innovativeness scores of our population; then we examined those who self-identified as an innovator versus those who did not to explore differences associated with innovativeness between these groups. Methods: A cross-sectional survey study of nurses in the US engaging in innovative behaviors was performed. We performed an exploratory factor analysis (EFA) to determine the correlates of innovative behavior. Results: Three-hundred and twenty-nine respondents completed the survey. Respondents who viewed themselves as innovators had greater exposure to HCD/DT workshops in the past year (55.8% vs. 36.6%, p = 0.02). The mean innovativeness score of our sample was 120.3 ± 11.2 out of a score of 140. The mean innovativeness score was higher for those who self-identified as an innovator compared with those who did not (121.3 ± 10.2 vs. 112.9 ± 14.8, p =< 0.001). The EFA created four factor groups: Factor 1 (risk aversion), Factor 2 (willingness to try new things), Factor 3 (creativity and originality) and Factor 4 (being challenged). Conclusion: Nurses who view themselves as innovators have higher innovativeness scores compared with those who do not. Multiple individual and organizational characteristics are associated with the innovativeness of nurses.